When gender norms and unions collide: effects on intrahousehold bargaining and labor supply - Pedreira, Sara Costa (2025)
This paper investigates the role of gender norms in shaping intra-household labor supply decisions, emphasizing their influence on women\'s bargaining power. Drawing on the collective household model by Chiappori et al. (2002), we use microdata from the 2015 Brazilian National Household Sample Survey (PNAD), focusing on dual-earner heterosexual couples. Gender norms are proxied by the share of domestic chores performed by women, a measure grounded in the literature on the gendered division of unpaid labor. To address the simultaneity between market and domestic labor decisions, we apply a GMM estimation strategy and employ union membership as an instrumental variable. Inspired by Small (2024), we argue that unions - through solidarity networks and social benefits - can shift men\'s engagement with socially reproductive labor, contributing to a more equitable household division of labor. Our findings indicate that traditional gender norms are associated with a significant reduction in women\'s labor supply, reinforcing the idea that persistent inequalities in unpaid work remain a key barrier to gender parity in the labor market.